Prolonged grief disorder: Nature, risk-factors, assessment, and cognitive-behavioural treatment - Boelen, Paul A.; Kolchinska, Yulia (Psychosomatic Medicine and General Practice, 2022)
Most people who are confronted with the death of a loved adjust without needing professional help. A significant minority of people confronted with loss develops symptoms of prolonged grief disorder (PGD), sometimes accompanied by bereavement-related post-traumatic stress disorder (PTSD) and depression. PGD is newly included in the psychiatric classification systems of the ICD-11 and DSM-5-TR. In Ukraine, many people are currently facing losses, in circumstances that may render them vulnerable to develop PGD and associated symptoms. In this article, we address “healthy” grief and discuss the nature, assessment, risk factors, and treatment of “unhealthy” grief, now referred to PGD. We also introduce a cognitive behavioural theory that helps to understand problematic psychological processes involved in the persistence and maintenance of PGD and that offers a clear framework for the application of all kinds of cognitive behavioural interventions and other treatment interventions that can be used to alleviate the pain of people with PGD. Examples of these interventions are described. Attention is paid to how the situation of war affects the development and treatment of PGD.